2005
DOI: 10.1186/1477-7525-3-41
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the psychometric properties of the Hospital Anxiety and Depression Scale in patients with breast cancer

Abstract: Background: To determine the psychometric properties of the Hospital Anxiety and Depression Scale (HADS) in patients with breast cancer and determine the suitability of the instrument for use with this clinical group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 54 publications
0
39
0
3
Order By: Relevance
“…This is in line with the recommendation to use broadly based fit indices [64]. While we have not used an instrument specifically designed to test each of the models, our methodology was similar to those of reports of other anxiety-depression screening questionnaires that have been used to test the models [20,23,26,39]. The use of these screening instruments is advantageous because it assesses the robustness of the models in widely used and validated questionnaires.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…This is in line with the recommendation to use broadly based fit indices [64]. While we have not used an instrument specifically designed to test each of the models, our methodology was similar to those of reports of other anxiety-depression screening questionnaires that have been used to test the models [20,23,26,39]. The use of these screening instruments is advantageous because it assesses the robustness of the models in widely used and validated questionnaires.…”
Section: Discussionmentioning
confidence: 60%
“…In a test of the model using other anxiety-depression screening instruments, the factors that emerged were also supportive [20,24,26,39]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Friedman et al (2001) also proposed a three-dimensional structure, derived from principal component analysis (using orthogonal and oblique rotations), which includes the psychomotor agitation (HADS-Anxiety Items 1, 7, and 11), psychic anxiety (HADS-Anxiety Items 3, 5, 9, and 13), ana the original HADSDepression subscales (see Table 1). The three-dimensional structures of the HADS stand out not only because of their theoretical foundation but also because in a number of confirmatory factor analyses, they meet the CFI and RMSEA criteria more so than the original two-dimensional structure and unidimensional structures (Barth & Martin, 2005;Desmond & MacLachlan, 2005;Dunbar et al, 2000;Martin et al, 2003;Rodgers et al, 2005). Some confirmatory factor analyses have suggested that Dunbar et al's model offers a superior fit to the data than Friedman et al's (2001) (Martin et al, 2003;Rodgers et al, 2005).…”
Section: Hads-totalmentioning
confidence: 92%